Peran Pendidikan Kewirausahaan dan Motivasi Berwirausaha Dalam Menumbuhkan Sikap Mental Kewirausahaan Pada Generasi Z - Putri, Berliana; Sunarya, Erry; Ramdan, Asep Muhammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to determine the effect of entrepreneurship education and entrepreneurial motivation on entrepreneurial mental attitude. Descriptive and associative methods with a quantitative approach. Sample determination using stratified sampling technique. The sample population amounted to 180 students in the city of sukabumi who were in the generation z age group. Multiple linear regression analysis techniques with the help of the SPSS version 26 application were used in this study. The results showed that entrepreneurship education and entrepreneurial motivation have a positive and significant effect on the entrepreneurial mental attitude in generation z.